A study of snake bite cases in Faridpur Medical College Hospital, Faridpur (Faridpur Medical College Journal, 2015)
Snakebite is one of the important cause of mortality in our country. This study was carried out to see the common type of snakes in local area with clinical presentations, complications and outcome of snake bite patients inFaridpur. Fifty cases of snakebite patients in medicine wards of Faridpur Medical College Hospital from 1st January 2012 to 31th April 2013 were studied. Among 50 snake bite patients 35 (70%) were male and 15 (30%) were female. Among them 30 (60%) were venomous and 20 (40%) snake bite cases were non-venomous.The common victims were farmers (53%) and housewives (13%). The bites were commonly encountered during rural foot walking (32%) followed by sleeping (15%). 55% were bitten during outdoor and agriculture related activities. 65% had sustained bite in lower limbs. The majority (82%) of the snakebites were observed during the month. Total 98% patients applied multiple tight tourniquets in the affected limb. A common local practice (seen in 85%) was to receive pre hospital treatment from 'Ohzas'. Among 30 poisonous cases, drooping of the upper eyelid, external ophthalmoplegia and brocken neck were the common features of poisoning. Among the 30 venomous snake bite cases 21 (70%) recovered completely after getting polyvalent antivenom serum and 9 (30%) died after admission. Total 80% cases recovered with 10 vials of polyvalent antivenom serum but others required upto 30 vials depending on severity of symptoms and its duration. No reaction to anti-snake venom was noticed.Faridpur Med. Coll. J. 2014;9(1): 32-34